2014
DOI: 10.1371/journal.pone.0101819
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Novel Drugs Can Effectively Improve Response, Delay Relapse and Enhance Overall Survival in Multiple Myeloma Patients with Renal Impairment

Abstract: BackgroundRenal impairment is a common feature in multiple myeloma and is considered a poor prognostic factor.AimTo determine the impact of novel drugs (i.e. bortezomib, lenalidomide and thalidomide) in the treatment of myeloma patients with renal impairment. The primary endpoint was overall survival and secondary endpoints were time to next treatment and response.MethodsThe study population included all patients diagnosed with treatment-demanding multiple myeloma January 2000 to June 2011 at 15 Swedish hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 26 publications
0
38
0
3
Order By: Relevance
“…The survival of patients with RI who were treated with bortezomib-based chemotherapy (60 months) was better than survival of those who received conventional agents (27 months) [20]. Mayo Clinic investigators reported a complete renal response rate in a higher proportion of patients treated with novel agents compared to conventional treatment.…”
Section: The Relationship Between Renal Function and Survival In MMmentioning
confidence: 99%
“…The survival of patients with RI who were treated with bortezomib-based chemotherapy (60 months) was better than survival of those who received conventional agents (27 months) [20]. Mayo Clinic investigators reported a complete renal response rate in a higher proportion of patients treated with novel agents compared to conventional treatment.…”
Section: The Relationship Between Renal Function and Survival In MMmentioning
confidence: 99%
“…3 Renal impairment in patients with MM is associated with shortened survival, but recovery of renal function during treatment may improve survival in these patients and even achieve similar outcomes in patients with a history of normal renal function. 3,4,7 The past several decades have seen advances in the treatment of MM, and outcomes have improved for patients with varying degrees of renal impairment; 3,8 despite this, most patients will ultimately relapse. 9,10 Control of MM via effective therapy has been shown to improve renal function in a large proportion of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Previous retrospective studies have indicated that a second ASCT is beneficial at relapse, at least if relapse occurs later than 18 months from initial treatment. 11 However, the development of novel drugs, for example, PI and IMiDs 1,[12][13][14][15] have raised the question if a second ASCT could be replaced by these drugs in second line. [16][17][18] A recent prospective study has shown that HDT followed by ASCT is superior to a cyclophosphamide-based regimen but data are lacking for comparing the novel drugs to ASCT.…”
Section: Introductionmentioning
confidence: 99%